Information security education -- towards a cybersecure society : 11th IFIP WG 11.8 World Conference, WISE 11, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-20, 2018, Proceedings /: 11th IFIP WG 11.8 World Conference, WISE 11, held at the 24th IFIP World Computer Congress, WCC 2018, Poznan, Poland, September 18-20, 2018, Proceedings. (2018) - Unknown
No abstract available